Мобільна архітектура як спосіб вирішення проблеми забезпечення внутрішньо переміщених осіб доступним житлом - Кубай, Роман; Кубай, Дзвенислава; Kubai, Roman; Kubai, Dzvenyslava (Видавництво Львівської політехніки, 2023)
У статті висвітлено проблеми створення та реалізації в Україні мобільного житла для внутрішньо переміщених осіб, що забезпечує людей гідним та комфортним притулком. Проектування аварійного житла вимагає інноваційного та гнучкого мислення, щоб забезпечити безпечне, здорове та комфортне житло. Це допоможе покращити якість житла для мешканців та навколишніх громад. Розглянуто підходи формування житлових збірно-розбірних конструкцій , які легко інтегруються в міське середовище. Висвітлено закордонний та український досвід проектування мобільної архітектури, здійснено аналіз поданих проектів.

The article highlights the problems of the creation and implementation of mobile housing for internally displaced persons in Ukraine, which provides people with a decent and comfortable shelter. In addition to social and cultural problems, refugees who are forced to relocate also deal with physical problems, where shelters are designed to meet the minimum needs of temporary accommodation. Designing emergency housing requires innovative and flexible thinking to ensure that housing is safe, healthy and comfortable. This would help improve the quality of housing for residents and surrounding communities. Portable architecture can help develop an industry-wide strategy that includes new materials, components, and construction methods. As a type of building project that must respond to relatively extreme operating parameters, it more often uses experimental and exploratory logistic and construction methods that may ultimately have more general significance. Portable buildings can do almost anything that permanent ones can, and they are also often able to perform other functions that would not be possible with other means. Portable buildings have a low environmental impact; they can be located in rural or urban areas with minimal long-term consequences. They can use a temporary identified address, which is valuable to both the operator and the visitor, as well-known locations can be used to increase the number of people reached over some time. Unusual forms of buildings that are temporarily placed in familiar settings can also change people's view of the environment and perhaps give them the impetus to recognize more clearly its positive and negative features.
Portable architecture as a way to solve the problem of providing internally displaced people with affordable housing
Keywords: внутрішньо переміщені особи (ВПО); мобільна архітектура; збірно-розбірні конструкції; модульна архітектура; доступне житло; internally displaced persons (IDPs); portable architecture; prefabricated constructions; modular architecture; affordable housing; 728.222